Aquatic life criteria & human health ambient water quality criteria derivations and probabilistic risk assessments of 7 benzenes in China. (July 2021) - Fan, Bo; Wang, Xiaonan; Xie, Zheyu; Li, Ji; Gao, Xiangyun; Cui, Liang; Gao, Shixiang; Liu, Zhengtao
Abstract: The benzenes have attracted worldwide attention due to their high biological toxicity in the environment. In this study, using species sensitivity distribution method to derive the aquatic life criteria of 7 benzenes (carbazole, 1, 3-Dichlorobenzene, 1, 4-Dichlorobenzene, 1, 2, 4-Trichlorobenzene, phenol, 2, 4-Dichlorophenol and nitrobenzene), then risk quotient method (RQ), potentially affected fraction (PAF) method and joint probability curve (JPC) method were applied for multilevel ecological risk assessment for 7 benzenes in Tai Lake Basin. In addition, the human health ambient water quality criteria (AWQC) of 7 benzenes were derived according to USEPA guidelines, and the probability distributions of human health AWQC for 7 benzenes in China were simulated by Monte Carlo simulation combined with crystal ball software. Finally, the health risks of 7 benzenes in Tai Lake were assessed by RQ method assisted by Monte Carlo simulation. The results showed that nitrobenzene had the maximum aquatic life criteria value, followed by phenol, chlorobenzenes, 2, 4-Dichlorophenol and carbazole. All recommended human health AWQC values of 7 benzenes were found at a position of 27th-55th percentiles in the output criteria distributions, indicating that recommended national human health AWQC values could provide effective protection for most of the population in China. Furthermore, the consumption of aquatic products was found to be the most influential parameter of human health AWQC for benzenes with higher Kow values. The risk assessments showed that noncarcinogenic 2, 4-Dichlorophenol had potential ecological risk, carcinogenic carbazole and 1, 2, 4-Trichlorobenzene had significant human health risk in Tai Lake. Graphical abstract: Image 1 Highlights: Probability distributions of human health AWQC values of 7 benzenes in China. Aquatic life criteria derivations for 7 benzenes in China. Multilevel ecological risk assessments for 7 benzenes in Tai Lake. Probabilistic risk assessment of human health for 7 benzenes in Tai Lake.